Exploring the Concept of Menyama Braya: The Cultural Heritage of Hindu and Islamic Communities in Pegayaman Village as a Multicultural Learning Medium - Suadnyana, Kadek Nova (Muslim Education Review, 2023)
The process of Islamic and Hindu acculturation and harmonious cultural lending in Pegayaman village interested the researchers in conducting this study. The concept of kinship or menyama braya is a concept that unites all differences in Pegayaman village. This study aims to determine (1) the existence of menyama braya in Pegayaman village; (2) the influence of menyama braya culture; (3) the process of internalizing the concept of menyama braya; and (4) the strategy of planting the concept of menyama braya. This study is prepared with qualitative research methods with three approaches, including geographical, socio-historical and cultural approaches used case study design. The results of this study show that the concept of menyama braya is very relevant to the current condition of society because this concept teaches people to remain respectful and have high tolerance even though they have different backgrounds, especially religious.